Zechariah a commentary on his visions and prophecies - Baron, David, 1855-1926 (Grand Rapids, MI Kregel, 2002)
Includes bibliographical references and indexes.
First published: London, UK : Hebrew Christian Testimony, 1918
Keywords: Bible. O.T. Zechariah -- commentaries